Pengaruh Kepemimpinan, Budaya Organisasi dan Motivasi Sebagai Variabel Intervening Terhadap Kinerja Pegawai - Hayati, Nur; Qadafi, Muammar; Fermita, Cut Nanda; Rizkina, Azka; Iskandar, Umar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study examines the influence of leadership, organizational culture on work motivation and employee performance, and examines the mediation effect of work motivation variables. The sample in this study was 160 permanent employees of PT. PLN (Persero) Lhokseumawe City Area. The analysis tool used was Amos. The results showed that each variable had a positive and significant influence. Leadership has a positive and significant effect on Work Motivation (p = 0.004) < α (0.05). Organizational Culture has a positive and significant effect on work motivation (p = 0.005) < α (0.05). Leadership has a positive and significant effect on employee performance (p = 0.030) < α (0.05). Organizational Culture has a positive and significant effect on employee performance (p = 0.044) < α (0.05). Work motivation has a positive and significant effect on employee performance (p = 0.001) < α (0.05). Work motivation mediates partial mediation between Leadership and Employee Performance (p=0.009) <α (0.05). Work motivation mediates partial mediation between Organizational Culture and Employee Performance (p=0.008) <α (0.05).